Environmentally friendly products factors that influence their adoption - Bhate, Seema
Past research has indicated that awareness of environmental issues is on the increase among consumers. It is, however, in doubt to what extent this concern for the environment ever translates into a change in everyday buying behaviour. An attempt has been made to clarify the situation using a combination of psychological, demographic and situational variables. Psychological variables studied are : innovativeness and adaptiveness as identified by KAI (Kirton's Adaption-Innovation Inventory) and involvement measured by Zaichowsky's PII (Personal Involvement Inventory). Demographic and situational factors include variables such as price, gender, age, availability. Personal interviews generated data from 148 respondents. The results indicate that the psychological and situational variables studied are important as far as environmentally friendly behaviour is concerned. It is seen that environmentally friendly behaviour correlates significantly with innovativeness. Involvement scores have been very low and are not statistically significant with any of the variables studied. This indicates that consumers are not yet involved enough in these issues. Further analysis emphasizes this point. Consumers are willing to pay a higher price for environmentally friendly products but are not ready to go out of their way to look for such products. Availability of these products has been rated much higher than price.
Consumers reputedly show an awareness of environmental issues in making purchasing decisions and the present study attempts to clarify the adoption of environmentally friendly products by an analysis of psychological, demographic and situational variables from a sample of 148 respondents.